THE INFLUENCE OF PERCEIVED BEHAVIORAL CONTROL, SOCIAL ENVIRONMENT, AND PERSONALITY ON ENTREPRENEURIAL INTENTION (CASE STUDY OF PRIVATE UNIVERSITY (PTS) STUDENTS IN JEMBER REGENCY) - Wulandary, Dian Anisa; Budi Santoso; Trias Setyowati (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: To test and analyze the influence of perceived behavioral control, social environment, and personality on entrepreneurial intention in students of Private Universities (PTS) in Jember Regency. Method: The study utilizes SPSS for data analysis to examine the relationship between perceived behavioral control, social environment, and personality with entrepreneurial intentions among students. Results: The findings indicate that perceived behavioral control, social environment, and personality all have a positive and significant influence on entrepreneurial intentions among students in private universities. Novelty: This perspective and analysis address gaps in existing research and offer practical contributions to local governments to reduce unemployment and encourage youth entrepreneurship.